Tyger tyger : a goblin wars book - Hamilton, Kersten, 1958- (Clarion Books, 2010)
Soon after the mysterious and alluring Finn arrives at her family's home, sixteen-year-old Teagan Wylltson and her disabled brother are drawn into the battle Finn's family has fought since the thirteenth century, when Fionn MacCumhaill angered the goblin king.